2019
DOI: 10.3389/fphys.2019.01096
|View full text |Cite
|
Sign up to set email alerts
|

Principles of Optogenetic Methods and Their Application to Cardiac Experimental Systems

Abstract: Optogenetic techniques permit studies of excitable tissue through genetically expressed light-gated microbial channels or pumps permitting transmembrane ion movement. Light activation of these proteins modulates cellular excitability with millisecond precision. This review summarizes optogenetic approaches, using examples from neurobiological applications, and then explores their application in cardiac electrophysiology. We review the available opsins, including depolarizing and hyperpolarizing variants, as we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
53
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(56 citation statements)
references
References 128 publications
(231 reference statements)
0
53
0
Order By: Relevance
“…As spontaneous beating can be inconsistent between the cells and wells, it is essential to control it by either electrical stimulation or by optical pacing. The so called optogenetics approach consists of expressing the channelrhodopsin-2 in hiPSC-CMs, which upon activation by a light source triggers electrical activity [42,43]. Combined with the MEA platform, this optical approach allows artifact-free stimulation for pacing cardiomyocytes.…”
Section: Technical Considerations For the Electrophysiological Characmentioning
confidence: 99%
See 2 more Smart Citations
“…As spontaneous beating can be inconsistent between the cells and wells, it is essential to control it by either electrical stimulation or by optical pacing. The so called optogenetics approach consists of expressing the channelrhodopsin-2 in hiPSC-CMs, which upon activation by a light source triggers electrical activity [42,43]. Combined with the MEA platform, this optical approach allows artifact-free stimulation for pacing cardiomyocytes.…”
Section: Technical Considerations For the Electrophysiological Characmentioning
confidence: 99%
“…Others have reviewed the technologies available to perform functional analysis of hiPSC-CMs in more detail [9,43,44]. Despite their differences in electrophysiological characteristics with adult human myocytes, hiPSC-CMs are generally considered as a predictive tool in the context of drug testing [39] and as a promising alternative to animal testing with regard to disease modeling ( Table 1).…”
Section: Technical Considerations For the Electrophysiological Characmentioning
confidence: 99%
See 1 more Smart Citation
“…Inhibitory optogenetic tools are light sensitive proteins or opsins which can be expressed in neurons to cause hyperpolarisation and silencing of spike firing 1,2 . Although several inhibitory optogenetic tools have been developed, there is no consensus regarding the best to use for either basic research or therapeutic applications.…”
Section: Introductionmentioning
confidence: 99%
“…Optogenetics is not only limited to the use of light-sensitive ion channels and pumps but the field is also being driven toward other light-sensitive proteins, such as G-protein modulating opsins ( Table 1; Ferenczi et al, 2019). In cardiac research, both natural and engineered versions of these opsins are being investigated to activate cell signaling with high temporal and spatial precision (Ferenczi et al, 2019). A recent study by Makowka et al (2019) has reported the utility of jellyfish opsin (JellyOp) to activate G s signaling in cardiomyocyte embryoid bodies and also in the intact mice hearts.…”
Section: Modulation Of Cell Signalingmentioning
confidence: 99%